Evanescent wave absorption based polyaniline cladding modified fiber optic intrinsic biosensor for glucose sensing application. (February 2015) - Pahurkar, V.G.; Tamgadge, Y.S.; Gambhire, A.B.; Muley, G.G.
Highlights: PANI cladding modified FOIGB has been developed for glucose sensing. Enzyme-GOx was immobilized on sensing element via glutaraldehyde cross-linking. Evanescent wave absorbance has been utilized to measure response and stability. FOIGB is highly selective toward glucose and has lowest detection limit of 10 nM. Abstract: Simple and novel evanescent wave absorption based cladding modified fiber optic intrinsic glucose biosensor (FOIGB) for glucose sensing has been developed and studied. The sensor was prepared by immobilization of glucose oxidase (GOx) by cross-linking via glutaraldehyde on a polyaniline (PANI) supportive matrix deposited on a core of optical fiber, which acts as an active cladding. The sensor operates in the intensity modulation scheme in which the absorbance was measured with respect to the changes in the glucose concentrations. The reaction between GOx and glucose changes the chemical environment of the sensing element, enhances π–π ∗ transition in PANI substrate that shows absorption peak at ∼272 nm. The response of the sensor is fast and requires very small volume of sensing analyte (∼1.5 ml). The sensor has shown very good sensitivity, repeatability and selectivity towards glucose, which makes it more suitable for commercialization. Under the selected optimal conditions, the sensor showed low detection limit of 10 nM in the measured range of 10 nM–100 mM concentrations of glucose in solution. Stability of the sensor was checked. It shows complete recovery after its use and worked very well upto 36 days with the same response. In addition, surface morphology of PANI film was studied by field emission scanning electron microscopy (FE-SEM).